PENGEMBANGAN KUALITAS SDM PADA BANK SYARIAH DALAM PERSPEKTIF SYARIAH: STUDI KASUS PT. BPRS HARTA INSAN KARIMAH BEKASI - Reza, Findia Lody; Khatimah, Husnul (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2011)
The purpose of this study was to determine the practice of human resource development in the BPRS Harta Insan Karimah and to determine the suitability of the development of human resources in the BPRS Harta Insan Karimah with the principles of human resource management in the Islamic perspective. The benefits of the research are expected to provide knowledge and insight in the world of Islamic banking in particular human resource development of shariah. The method used is a qualitative method of naturalistic techniques of data retrieval is a field study that includes observation and interviews, library research and triangulation. The conclusion from this study showed that human resource development conducted in the BPRS Harta Insan Karimah Bekasi is in conformity with Islamic perspective.